Influência Do Coacervado De Proteínas Do Soro Do Leite E Galactooligossacarídeo Na Resposta Inflamatória, Perfil Dos Fosfolipídeos E Microbiota Intestinal Em Camundongos Com Obesidade Induzida Por Dieta - Amaral, Juliane Suzuki [UNIFESP] (2018)
Whey protein products such as Coacervate whey protein (Coa), galactooligosaccharide (Gos) and both associated (COAG) were tested in mice fed with a high fat diet to verify changes on enterocyte structural lipid profile, inflammation and intestinal microbiota composition during obesity. Males C57BL/6 were fed normolipid and high fat diets, divided into five experimental groups: 1) Normolipid control (Nwater), 2) High fat control (HFwater), 3) High fat + Coa (HFCoa), 4) High fat + Gos (HFGos) and 5) High fat Coa + Gos (HFCOAG), for 16 weeks treatment. Stool samples were collected at the end of the experiment and frozen in cryotubes for metagenomic analysis. The intestine was divided in: duodenum, cecum and colon, frozen in cryotubes until the processing data for cytokine dosage, evaluation of TLR4 protein and the main classes of fatty acid profile: phosphatidylcholine (PC), phosphatidylethanolamine (PE) and sphingomyelin (SM). The biometric data showed that HFCoa and HFCOAG groups maintained the same body mass gain as normolipid control, but only HFCOAG decreased adiposity and energy efficiency compared HFwater. The different diets changed the gut microbiota. Among treatments, the composition of the HFCOAG gut microbiota was closer to normolipid control group showing high percentages of dissimilarity for healthy state bacteria such as Lachnospiracea and Porphyromonas and the taxon RF39 as microbial signature. HFCoa group showed the best anti-inflamatory activity in the cecum (IL / 10 / TNFα). HFGos group decreased IL-1β with concomitant high levels of IFNγ, which correlated positively with Bilophila genus suggesting an influence of this taxon on IFNγ production. The percentage of vaccenic acid (18: 1n7) in the SM class of colon membrane increased in all treatments showing its possible relation with lipid raft instability on TLR4 activation. TLR4 receptors showed no difference in its expression, but changes on its activation is inferred since a decrease of the IL-6 was observed in this tissue. HFCOAG treatment increased vaccenic and myristoleic acid (14: 1n9) in SM class demonstrating correlations with an improvement of anti-inflammatory activity in colon. The increase of vaccenic acid was correlated to the Mogibacteriacea taxon. HFGos treatment increased palmitoleic acid (16: 1n7) in PC class, which was negatively correlated with an anti-inflammatory activity in colon. In general, there was a clear diet influence that directly promotes changes in gut microbiota profile and alters metabolic response during obesity as consequence. COAG showed the best preventive response among treatments in this research, but more studies are necessary to evaluate other metabolic aspects in different tissues and on the development of this compound that may be used as a prophylactic against obesity in the future.